THE ROLE OF SUPRASEGMENTAL FEATURES IN ENGLISH INTONATION PATTERNS: A PHONOLOGICAL PERSPECTIVE - Azhara Dwi Lathifah; Firza Sakinah; Selamat Husni (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2025)
This study explores the role of suprasegmental features, particularly intonation patterns, in English phonology. While segmental features like vowels and consonants have received extensive attention in linguistic research, suprasegmentals, including intonation, stress, rhythm, and pauses, are often less emphasized despite their critical role in shaping communication. Intonation, as a key suprasegmental feature, helps convey meaning, emotional tone, and grammatical structure in spoken English. This paper discusses how intonation patterns not only differentiate sentence types (e.g., statements vs. questions) but also express emotions and attitudes. Furthermore, it highlights the significance of understanding intonation in intercultural communication, where variations in pitch patterns can lead to misunderstandings. The paper concludes by emphasizing the need for further research on suprasegmentals and their application in language learning and speech technology.